3D graphics for game programming - Han, JungHyun (Chapman and Hall/CRC, 2011)
"Many of computer graphics classes in colleges are focused on real-time rendering and animation. However, it is not easy to nd an appropriate textbook, which presents the state of the art in interactive graphics, is balanced between theory and practicality, and is of a proper length to be covered in a semester. This book is written for answering the need and presents the must-know in interactive graphics. This book ts the advanced undergraduate or beginning graduate classes for 'Computer Graphics' and 'Game Programming.' Another primary reader group of this book may be composed of game developers, who have experience in graphics APIs and shader programming but have felt lack of theoretical background in 3D graphics. A lot of programming manual-like books can be found in the bookstore, but they do not provide a sufficient level of mathematical background for the game developers. Assuming that the readers have minimal understanding of vectors and matrices, this book provides an opportunity to combine their experiences with the background theory of computer graphics"-- Provided by publisher.